PERBEDAAN KOMPETENSI SOSIAL PADA REMAJA PRIA DAN REMAJA WANITA - Melani Aprianti (Biopsikososial: Jurnal Ilmiah Psikologi Fakultas Psikologi Universitas Mercubuana Jakarta, 2019)
The research was conducted aimed at finding out whether there were differences in social competence in young men and young women. The method used in this study is quantitative with the number of respondents amounting to 154 people, consisting of 74 young men and 80 young women. In this study the respondents used were psychology faculture students at the Jakarta Mercubuana University. The measuring instrument used in this study is the social competence scale based on Gresham & Elliot. And the tests carried out in this study based onIndependen Sample  T-Tes obtained sig, 0,000 or less than <0.05. Which means H1 is accepted by H0 rejected. From this explanation, it can be concluded that there is a difference between the adolescent male competency with the social competence of young women.